An epidemiologic study of eclampsia - S. Porapakkham (2018)
The epidemiologic characteristics of 298 cases of eclampsia treated from 1967 to 1974 in the Siriraj Hospital, Bangkok, Thailand, are described. The incidence of eclampsia was 0.2% of all deliveries, and the nulliparas had a higher incidence than the multiparas in all age groups. About 90% of patients had inadequate or no antenatal care, and 43% of patients suffered their first convulsion after admission to the hospital. Although the patient's own neglect was the major causative factor, physician error played some role in the development of eclampsia. The maternal mortality rate was 4.7%, and factors influencing maternal and perinatal death rates are discussed. The rate of cesarean section for eclamptics was 7%, as compared to a 3% rate for the general obstetric population. The findings suggest that more frequent use of properly time cesarean section can improve the outlook for both the fetus and mother. An active program aimed at reducing the incidence of eclampsia and its maternal and perinatal mortality is emphasized.